Kontrol Bandwidth Dinamis Berbasis Algoritma Logika Fuzzy pada Jaringan Wireless Ad-Hoc - Yedidio Purwodwiyogo; Alif Subardono (Ikatan Ahli Informatika Indonesia (IAII), 2018)
Ad-Hoc network is a wireless network consisting of a collection of nodes that are connected spontaneously and dynamically. With the character of the Ad-Hoc network, this network is often used in the development of IoT devices (Internet of Things) or emergency conditions. But in the implementation of the Ad-Hoc network there are challenges that need to be addressed, one of which is the very limited bandwidth that can be provide. The existence of these things will lead to new problems, when network traffic is very busy, it will reduce the fairness level of bandwidth distribution. Therefore, the implementation of fuzzy logic is proposed as a reliable decision maker in managing bandwidth. From the results found in this study prove that the results of the obtained throughput performance is not found to be a significant increase, but the jitter and packet loss produces a better value than when the bandwidth management system is applied.